1979
DOI: 10.1107/s0567739479002175
|View full text |Cite
|
Sign up to set email alerts
|

The defect structure of VOx. II. Local ionic arrangements in the disordered phase

Abstract: In VO x (0.8 < x < 1.3), there are large numbers of cation and anion vacancies and interstitial vanadium ions. To determine the local arrangements of these defects, X-ray diffuse scattering was measured in absolute units with single crystals of VO x (x = 0.89, 1.17 and 1.28). For x > 1, the interstitials are present near vacancy clusters, similar to the defect arrays found in the semiconductor FexO. For x < 1, there are few interstitials, but an increased concentration of anion vacancies. The anion and cation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

1983
1983
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 21 publications
0
8
0
2
Order By: Relevance
“…4,5 For the last 20 years VO x has been used as the active material in uncooled infrared imaging detectors operating in the pulsed bias readout mode [1][2][3] and have been contradictorily reported as having amorphous 6 and polycrystalline 7 structure, with nonstoichiometries 8 and mixed-oxides. 9 Recent evidence has indicated that the true nature of the microstructure of VO x for microbolometer applications is a composite of rock-salt face centered cubic (fcc) vanadium monoxide phase [10][11][12][13][14] nanocrystallites, where the oxygen content "x" in VO x can vary from 0.8 < x < 1.3, and an amorphous component present between the crystallites. Similarly, room-temperature monoclinic, high-temperature (>68 C) rutile vanadium dioxide, used for its relatively sharp temperature-dependent shift in resistivity and transmittance denoted as the metal-to-semiconductor transition, may contain higher x amorphous material between crystallites present in thin film forms of interest for new "phase change" applications.…”
mentioning
confidence: 99%
“…4,5 For the last 20 years VO x has been used as the active material in uncooled infrared imaging detectors operating in the pulsed bias readout mode [1][2][3] and have been contradictorily reported as having amorphous 6 and polycrystalline 7 structure, with nonstoichiometries 8 and mixed-oxides. 9 Recent evidence has indicated that the true nature of the microstructure of VO x for microbolometer applications is a composite of rock-salt face centered cubic (fcc) vanadium monoxide phase [10][11][12][13][14] nanocrystallites, where the oxygen content "x" in VO x can vary from 0.8 < x < 1.3, and an amorphous component present between the crystallites. Similarly, room-temperature monoclinic, high-temperature (>68 C) rutile vanadium dioxide, used for its relatively sharp temperature-dependent shift in resistivity and transmittance denoted as the metal-to-semiconductor transition, may contain higher x amorphous material between crystallites present in thin film forms of interest for new "phase change" applications.…”
mentioning
confidence: 99%
“…The fact that vacancies exist on possible Fe sites only underlines this possibility, as the best O 2À ion conductors, for example, d-Bi 2 O 3 [21,22] and yttriastabilized zirconia (YSZ), [23,24] have oxygen-deficient fluorite structures. Furthermore, the tetrahedral slabs in the oxygenion-conducting brownmillerites, [25,26] for example, Ca 2 FeAlO 5 , even have a close anti-type structural relation with the title compounds.…”
Section: Metal Vacancy Ordering In An Antiperovskite Resulting In Twomentioning
confidence: 99%
“…Розвиток методики дифузного розсіяння дозволяє дослідити також тверді роз-чини втілення (див. бібліографію в [128,156,164,166,224,225,[238][239][240][241][242][243][244][245][246][247][248]) та більш складні системи, що містять декілька нееквівалентних вузлів в елементарній комірці [44][45][46], і навіть розчини органічних спо-лук [47,93].…”
Section: сплавunclassified